“Efecto de adaptación de ocho genotipos de arroz (oryza sativa) al trasplante en tres localidades del bajo mayo” - Huamán Soria, Hugo Alberto (2001)
The present work of Investigation had ace objective to identify the adaptability of 05 promissory lines of ruffles that you/they it combines high yield potential, precosidad you intermediates you yourself, good quality molinera and that they adapt to the conditions agroclimáticas of the V alley of the Low May. The realization of the Plan of Cruzamiento, handling and evaluation of the material segregante were developed in the Experimental Stations of "Vista Florida" (Chiclayo) and "The Porvenir"-Tarapoto from l 994 up to the 2 000. The handling of the materials in you intermediates you yourself generations and outposts continued being canied out in Experimental the Station "El Porvenir"-Tarapoto. The rehearsals yield multilocales were executed in field of Farmers in the Bajo Mayo Valley, to determines the interaction genotipo for environment in three towns: Juan Guerra, Chontamuyo and Cacatachi in the Valley of the Low May in the years 1 999 and 2 000. Inside the genotipos that were identified with better behavior agronomic, good yield potential and good quality of grain, it corresponds the first place to the line PNA2002-HU4-2-EP1-l.